Wound care at a glance / Ian Peate, Melanie Stephens - Peate, Ian
"Care of wounds is an important clinical subject for nursing students, and is an essential nursing skill. It is a subject that is just as important within hospitals, as in community settings. The field of skin care and skin protection is central to the discipline of nursing. Care of wounds is currently a hot topic in healthcare, and much is happening to raise awareness of the issue of hospital-acquired pressure ulcers. Any damage leading to a break in the continuity of the skin can be called a wound- it is not a frequent problem for most healthy people but is a threat to older people; to patients with restricted mobility, chronic illnesses, or trauma; and to those undergoing invasive procedures. To protect the skin and manage wounds effectively, the nurse must understand the factors affecting skin integrity, the physiology of wound healing and specific measures that promote optimal skin conditions. An accessible, visual take on a hot topic of healthcare"